Jane Eyre - Bronte, Charlotte, 1816-1855; Series Editor Das, Bikram K. (India Orient Black Swan, 2011)
Despite her plainness, Jane captures the heart of her enigmatic employer, Edward Rochester, but soon discovers he has a secret that could jeopardize any hope of happiness between them.
Include Colour Illustration
Keywords: Governesses -- England -- Mentally ill women -- Orphans -- Young women -- Charity-schools -- Fathers and daughters -- Country homes